Primary prevention of stroke in children with sickle cell anemia in sub-Saharan Africa: rationale and design of phase III randomized clinical trial. (24th November 2020) - Abdullahi, Shehu U.; Wudil, Binta J.; Bello-Manga, Halima; Musa, Aisha B.; Gambo, Safiya; Galadanci, Najibah A.; Aminu, Hauwa; Tijjani Gaya, Aliyu; Sanusi, Surayya; Tabari, Musa A.; Galadanci, Aisha; Borodo, Awwal; et al.
Abstract: Strokes in children with sickle cell anemia (SCA) are associated with significant morbidity and premature death. Primary stroke prevention in children with SCA involves screening for abnormal transcranial Doppler (TCD) velocity coupled with regular blood transfusion therapy for children with abnormal velocities, for at least one year. However, in Africa, where the majority of children with SCA live, regular blood transfusions are not feasible due to inadequate supply of safe blood, cost, and the reluctance of caregivers to accept transfusion therapy for their children. We describe the Primary Prevention of Stroke in Children with Sickle Cell Disease in Nigeria Trial [ S troke Pr evention i n N i g eria (SPRING) trial, NCT02560935], a three-center double-blinded randomized controlled Phase III clinical trial to 1) determine the efficacy of moderate fixed-dose (20 mg/kg/day) versus low fixed-dose (10 mg/kg/day) hydroxyurea therapy for primary stroke prevention; 2) determine the efficacy of moderate fixed-dose hydroxyurea for decreasing the incidence of all cause-hospitalization (pain, acute chest syndrome, infection, other) compared to low fixed-dose hydroxyurea. We will test the primary hypothesis that there will be a 66% relative risk reduction of strokes in children with SCA and abnormal TCD measurements, randomly allocated, for a minimum of three years to receive moderate fixed-dose versus low fixed-dose hydroxyurea (total n = 220). The results of this trial will advance the care of children with SCA in sub-Saharan Africa, while improving research capacity for future studies to prevent strokes in children with SCA.